Evolutionary footprints of cold adaptation in arctic-alpine Cochlearia (Brassicaceae) - evidence from freezing experiments and electrolyte leakage - Eisenschmid, Karolin; Jabbusch, Sarina; Koch, Marcus (Perspectives in plant ecology, evolution and systematics, 2023)
As global warming progresses, plants may be forced to adapt to drastically changing environmental conditions. Arctic-alpine plants have been among the first to experience the effects of climate change. As a result, cold acclimation and freezing tolerance may become increasingly crucial for the survival as winter warming events and earlier snowmelt will cause increased exposure to occasional frost. The tribe Cochlearieae in the mustard family (Brassicaceae) offers an instructive system for studying cold adaptation in evolutionary terms, as the two sister genera Ionopsidium and Cochlearia are distributed among different ecological habitats throughout the European continent and the far north into circumarctic regions. By applying an electrolyte leakage assay to leaves obtained from plants cultivated under controlled temperature regimes in growth chambers, the freezing tolerance of different Ionopsidium and Cochlearia species was assessed measuring lethal freezing temperature values (LT50 and LT100), thereby allowing for a comparison across different species and accessions in their responses to cold. We hypothesized that, owing to varying selection pressures, geographically distant species would differ in freezing tolerance. Despite Ionopsidium occurring under warm and dry Mediterranean conditions and Cochlearia species distributed often at cold habitats, all accessions exhibited similar cold responses. The results may indicate that physiological adaptations of primary metabolic pathways to different stressors, such as salinity and drought, may confer an additional tolerance to cold; this is because all these stressors induce osmotic challenges.
Online verfügbar: 16. März 2023, Artikelversion: 17. März 2023
Gesehen am 21.09.2023